Flexural behavior of hybrid fibre-reinforced geopolymer composites (FRGC)-jacketed RC beams - Guades, Ernesto J.; Stang, Henrik; Schmidt, Jacob W.; Fischer, Gregor (Engineering structures, 2021)
•FRGC-jacketing technique increased the loading performance of RC beams.•FRGC-jacketed beams exhibited high energy absorption capacity.•The flexural strength of FRGC-jacketed beams was modelled analytically. Fibre-reinforced geopolymer composites (FRGC) are drawing interest as potential repairing and strengthening materials for concrete elements due to their desirable properties. They are known to have good mechanical bond with the concrete substrate and steel reinforcement, good fire resistance, greater durability in corrosive environments, and lower creep and shrinkage characteristics. However, the main challenge in their practical application is the lack of design standards and the structural performance of FRGC-rehabilitated concrete elements has not been fully investigated. In this paper, the result obtained from an experimental study on the flexural behavior of reinforced concrete (RC) beams jacketed by hybrid FRGC is reported. Six repair and strengthening configurations were adopted in this study including jacketing at the bottom, two and three sides of the beam with at least 25 mm thick FRGC layer. Twelve FRGC-jacketed and two control beams were subjected to four-point bending test to determine their loading performance, cracking response, ductility and energy absorption capacity. In addition, an analytical model was developed to predict the ultimate moment capacity of the jacketed beams. The results showed that FRGC-jacketing technique increased the cracking, yielding and ultimate load of the initial RC beams by up to 167%, 62% and 62% respectively. Among the seven repair and strengthening patterns, the bottom and three-sides jacketing provided less ductile response, nevertheless, it offered a 32% increase on the energy absorption value of the initial RC beam. It also indicated that all jacketed RC beams displayed no sign of overlay delamination up to failure, confirming a bond excellence between the FRGC and concrete substrate. The model predicting the flexural moment capacity of the FRGC jacketed beams compared reasonably with the experimental results with error value of 4–7%.